ESRA19-0414 The effect of intravenous dexamethasone on the anaesthetic characteristics of peripheral nerve block: a double-blind, randomized control, dose-response volunteer study. (30th August 2019) - Black, N; Short, A; El-Boghdadly, K; Clarke, H; Jin, R; Chin, KJ; Chan, V
Abstract : Background and aims: Intravenous (IV) dexamethasone is thought to prolong sensory and motor anesthesia after peripheral nerve blocks. A volunteer study was performed to evaluate the dose-response relationship of IV dexamethasone on ultrasound-guided median nerve block. Methods: In this double-blinded, placebo-controlled, randomized controlled study, 18 ASA 1 volunteers received two median nerve blocks with 0.25% bupivacaine separated by a minimum of two weeks and either IV dexamethasone (2 mg, 4 mg or 8 mg) or IV saline on each study occasion. Quantitative testing (QST) was performed. The primary outcome was time to return of normal pinprick sensation. Secondary outcomes included: time to return of cold detection threshold (CDT), warm detection threshold (WDT), cold pain threshold (CPT), and heat pain threshold (HPT). Ethical approval was obtained. Results: There was no difference in time to recovery of pinprick testing or CDT, WDT, CPT and HPT between groups receiving IV saline or IV dexamethasone, irrespective of dose. However, area under QST curves indicated prolongation of CDT (0 mg vs. 8 mg, p = 0.0019) and WDT (0 mg vs. 2 mg, p=0.0084, 0 mg vs. 4 mg, p=0.0011 and 0 mg vs 8 mg, p<0.0001). Conclusions: IV dexamethasone did not significantly prolong the time to return of pinprick sensation or return of cold and heat pain threshold although there was prolongation of the time to return of cold and warm touch detection. These results contrast clinical studies which show that IV dexamethasone prolongs analgesia after a peripheral nerve block. We hypothesize that the clinical effect might be due to mechanisms independent of direct nerve block prolongation.